2022
DOI: 10.4329/wjr.v14.i8.293
|View full text |Cite
|
Sign up to set email alerts
|

Imaging volumes during COVID-19: A Victorian health service experience

Abstract: BACKGROUND The World Health Organisation declared the coronavirus disease 2019 (COVID-19) a pandemic on March 11, 2020. While globally, the relative caseload has been high, Australia’s has been relatively low. During the pandemic, radiology services have seen significant changes in workflow across modalities and a reduction in imaging volumes. AIM To investigate differences in modality imaging volumes during the COVID-19 pandemic across a large Victorian public health n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Ultrasound, mammography, and magnetic resonance imaging (MRI) were the modalities most affected during this period [18]. A study of imaging volume across Victoria, Australia, noted a 20.7% decrease in imaging volume between 11 March 2020 and 21 April 2020 compared with the same timeframe in 2019 [10]. The subsections of nuclear medicine, mammography, and magnetic resonance imaging had the largest decreases in volume [10].…”
Section: Volumementioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound, mammography, and magnetic resonance imaging (MRI) were the modalities most affected during this period [18]. A study of imaging volume across Victoria, Australia, noted a 20.7% decrease in imaging volume between 11 March 2020 and 21 April 2020 compared with the same timeframe in 2019 [10]. The subsections of nuclear medicine, mammography, and magnetic resonance imaging had the largest decreases in volume [10].…”
Section: Volumementioning
confidence: 99%
“…A study of imaging volume across Victoria, Australia, noted a 20.7% decrease in imaging volume between 11 March 2020 and 21 April 2020 compared with the same timeframe in 2019 [10]. The subsections of nuclear medicine, mammography, and magnetic resonance imaging had the largest decreases in volume [10]. A multicenter survey of chest CT scans in Iran between 2019 and 2020 found that there was a 50.2% increase in chest CT volume compared with 2018 to 2019.…”
Section: Volumementioning
confidence: 99%
See 1 more Smart Citation